Carbon Doping: In‐Situ Carbon Doping of TiO2 Nanotubes Via Anodization in Graphene Oxide Quantum Dot Containing Electrolyte and Carburization to TiOxCy Nanotubes (Adv. Mater. Interfaces 5/2015). Issue 5 (March 2015) - Favaro, Marco; Leonardi, Silvia; Valero‐Vidal, Carlos; Nappini, Silvia; Hanzlik, Marianne; Agnoli, Stefano; Kunze‐Liebhäuser, Julia; Granozzi, Gaetano
Abstract : In article 1400462 S. Agnoli, J. Kunze‐Liebhäuser, and co‐workers report on the anodic production of self‐organized titania nanotubes in an electrolyte, enriched with graphene oxide quantum dots, where composites grown under these conditions show in‐situ carbon doping, leading to substoichiometric oxide and TiC formation. It is possible to gradually tune the density of states below the Fermi level of the nanotubular composites, which can be referred to as band‐gap engineering.